The Silent Epidemic: Unmasking Community Risk Factors For Non-Communicable Diseases - John Leones Damo; Adriane Gabrille Perez (Health Gate, 2026)
Non-communicable diseases (NCDs) such as cardiovascular illnesses, diabetes, cancer, and chronic respiratory conditions have emerged as a silent epidemic, affecting millions globally and increasingly impacting Filipino communities. This study, titled "The Silent Epidemic: Unmasking Community Risk Factors for Non-Communicable Diseases", aimed to identify and analyze the behavioral, environmental, socioeconomic, and healthcare-related risk factors contributing to the prevalence of NCDs in selected communities within the Cagayan Valley Region. A quantitative descriptive research design was employed, using a structured questionnaire administered to adult residents aged 18 and above through purposive sampling. The instrument gathered data on lifestyle practices, environmental conditions, access to healthcare, and cultural influences. Statistical analysis, including descriptive statistics and chi-square tests, was conducted using SPSS to identify significant trends and associations among variables. Findings revealed that limited access to healthy food options, sedentary lifestyles, economic hardship, and inadequate healthcare access are key contributors to increased NCD risk in the region. Social norms and cultural perceptions were also found to influence individual health behaviors, either promoting or hindering healthy living. The study underscores the urgent need for community-based health education, improved infrastructure, and targeted interventions that address the root causes of NCDs. By highlighting these risk factors, the research aims to support policymakers, health professionals, and community leaders in developing strategies to prevent and reduce the burden of non-communicable diseases in vulnerable populations.